Need of Smart Automation, IOT and Secured Network in Industry 4.0 - Jasjeet Singh, C. Banerjee, Santosh K. Pandey (Mathematical Statistician and Engineering Applications, 2022)
The Industry 4.0 is totally based on the innovative technologies such as IOT, IIOT, Machine Learning, AI, Business Analysis technologies. Data plays most important to get results, to apply industry 4.0 we must identify the data to start any process. In the last research work we have mentioned about following a process designed by us, to start the same we need to input data. The sensors of IIOT require a key program to manage specific applications. The necessary data will naturally depend on specific type of industry we ideally want to implement industry 4.0. Currently, data security remains a considerable concern for all the industries. To comply with standards set by Industrial Authorities in India some programs have been designed and produced to provide Network Connectivity, Data Transmission, Network Security, Data Security, Threat Alerts, Threat Detection, Network flow. In this study we showcased a survey propagated with experts from different industries which are into business of producing Automobiles, Automobile Parts, Shipping vessels and Cargo, Railways Parts, Clothing Industries, Electronic chips & circuits, Recycled products. The survey is based on a set of questions which have help to understand the Past practices, present trends and future scope in the industry by introducing cutting edge technologies, Latest machinery and Fully Equipped Systems.